2011
DOI: 10.1136/oemed-2011-100220
|View full text |Cite
|
Sign up to set email alerts
|

Has European Union legislation to reduce exposure to chromate in cement been effective in reducing the incidence of allergic contact dermatitis attributed to chromate in the UK?

Abstract: The timing of this significant decline in the UK incidence of chromate attributed ACD, and the greater decline in workers potentially exposed to cement strongly suggests that the EU Directive2003/53/EC was successful in reducing exposure to chromate in cement in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
60
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 9 publications
3
60
0
3
Order By: Relevance
“…A greater post intervention decline for HCWs than non-HCWs might be expected, as HCWs are mainly employed within the National Health Service, which has better access to occupational health medical specialist advice and service provision than other workers 9. Post intervention results for non-HCWs for both ‘latex’ and control (non-‘latex’) cases (Groups 5 and 6) are generally encouraging; these findings may be because of interventions aimed at ‘latex’ or other workplace exposures,23 or as a result of specific campaigns by enforcement agencies including the Health and Safety Executive, which have been aimed at Small and Medium Sized Employers (eg, Bad Hand Day aimed at the hairdressing industry, launched in 2006) 24…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A greater post intervention decline for HCWs than non-HCWs might be expected, as HCWs are mainly employed within the National Health Service, which has better access to occupational health medical specialist advice and service provision than other workers 9. Post intervention results for non-HCWs for both ‘latex’ and control (non-‘latex’) cases (Groups 5 and 6) are generally encouraging; these findings may be because of interventions aimed at ‘latex’ or other workplace exposures,23 or as a result of specific campaigns by enforcement agencies including the Health and Safety Executive, which have been aimed at Small and Medium Sized Employers (eg, Bad Hand Day aimed at the hairdressing industry, launched in 2006) 24…”
Section: Discussionmentioning
confidence: 91%
“…Importantly, other coincidental events need to be taken into account when interpreting results; examples relevant to this study include the introduction of European Union legislation to reduce exposure to chromate in cement,23 and specific campaigns by enforcement agencies 24. Additionally, as some estimated changes in incidence based on volunteer reporting may be biased by reporter fatigue, apparent downward trends need to be interpreted cautiously 28.…”
Section: Discussionmentioning
confidence: 99%
“…Our data describe the secular trends in OD in Europe during a period when improving working conditions was given a high priority but our data and methods could also be used for formal evaluation of the impact of interventions. For example, in the UK, these data were used to show a positive impact of the EU chromate directive 37. Future work using these Europe-wide data might provide insight into the impact of the EU vibration directive38 on vibration-related OD.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have demonstrated the robustness of their data, as for instance, when they were able to identify the effects on disease incidence of specific European Union regulations focused on prevention (eg, the decrease in cement contact dermatitis2). This team is also at the forefront of the identification and management of bias (eg, their previous work on ‘reporter fatigue’3).…”
mentioning
confidence: 98%